2022
DOI: 10.3390/horticulturae8050359
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron Induced In Vitro Clonal Propagation of Lagerstroemia speciosa (L.) Pers.—An Important Avenue Tree

Abstract: A high throughput regeneration protocol has been developed for Lagerstroemia speciosa through node explants under the regime of various plant growth regulators (PGRs). This protocol can provide an alternative mode to seed-grown plants and minimize the cost–time of regeneration, significantly. Murashige and Skoog (MS) medium containing various combinations of PGRs exhibited a marked stimulatory effect on morphogenesis. Of the various combinations tried, node explant pretreated with thidiazuron (TDZ; 5.0 µM) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The supplementation with TDZ in the culture media efficiently activated the antioxidant system in the in vitro raised shoots, leading to maximum production of total phenolic content, total flavonoid content, antioxidant enzymes and lignans [ 55 ]. In a recent study, TDZ was shown to be effective in inducing in vitro clonal propagation of Lagerstroemia speciosa (L.) Pers., commonly known as ‘Pride of India’ or ‘Banaba’, belonging to the family Lythraceae, and is an important avenue tropical deciduous tree widely distributed in the Philippines, Malaysia, India, Vietnam, and China [ 56 ]. Furthermore, TDZ has induced efficient in vitro organogenesis and regeneration of Scutellaria bornmuelleri , a medicinal plant belonging to the Scutellaria genus of the Lamiaceae family, endemic in the East Azerbaijan province of Iran, used in traditional medicines to treat constipation, wound healing, and stress [ 57 ], and has increased shoot induction and proliferation rate of Tecoma stans L. (Bignoniaceae), commonly known as Ginger-Thomas, a plant endowed with antitumor, antioxidant, antimicrobial, antidiabetic and free radical scavenging properties [ 58 ].…”
Section: Thidiazuron (Tdz)mentioning
confidence: 99%
“…The supplementation with TDZ in the culture media efficiently activated the antioxidant system in the in vitro raised shoots, leading to maximum production of total phenolic content, total flavonoid content, antioxidant enzymes and lignans [ 55 ]. In a recent study, TDZ was shown to be effective in inducing in vitro clonal propagation of Lagerstroemia speciosa (L.) Pers., commonly known as ‘Pride of India’ or ‘Banaba’, belonging to the family Lythraceae, and is an important avenue tropical deciduous tree widely distributed in the Philippines, Malaysia, India, Vietnam, and China [ 56 ]. Furthermore, TDZ has induced efficient in vitro organogenesis and regeneration of Scutellaria bornmuelleri , a medicinal plant belonging to the Scutellaria genus of the Lamiaceae family, endemic in the East Azerbaijan province of Iran, used in traditional medicines to treat constipation, wound healing, and stress [ 57 ], and has increased shoot induction and proliferation rate of Tecoma stans L. (Bignoniaceae), commonly known as Ginger-Thomas, a plant endowed with antitumor, antioxidant, antimicrobial, antidiabetic and free radical scavenging properties [ 58 ].…”
Section: Thidiazuron (Tdz)mentioning
confidence: 99%
“…However, many woody plants, including crapemyrtle, exhibit recalcitrance in the in-vitro organogenic process, necessitating resource-intensive experiments to nd the optimal balance of PGRs to promote organogenesis (Benson 2000;Bonga 2017;Long et al 2022;Tanimoto and Harada 1984;Thorpe and Harry 1990). Previous studies on micropropagation of L. speciosa, focused on the effects of various PGRs including thidiazuron (TDZ), 6-benzyladenine (6-BA), -naphthalene acetic acid (NAA), and N6-(3-hydroxybenzylamino purine) (meta-Topolin) (Ahmad et al 2022a;Ahmad et al 2022b; Lim-Ho and Lee 1985; Vijayan et al 2015), but few studies have examined callus-induced regeneration from leaf explants (Rahman et al 2010). A comprehensive investigation to optimize PGR combinations for callus induction, adventitious bud differentiation, shoot proliferation, and the subsequent rooting of regenerated plantlets is a crucial rst step in developing methodologies to apply modern breeding tools to L. speciosa and other taxa.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of such new species as ornamental crops can be facilitated by the existence of a simple, productive and low-cost propagation protocol. Micropropagation using in vitro grown seedlings as starting material is a widespread method for the establishment of in vitro cultures, as it overcomes culture infection problems, reduces time needed for the establishment of in vitro cultures and usually leads to high proliferation rates [9,10,13,[20][21][22][23][24]. On the other hand, in vitro propagation initiated from seedlings can have a positive effect on the genetic diversity of the produced material compared to the use of other type of explants.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, in addition to other cytokinins, the effect of thidiazuron (TDZ) (non-purine cytokinin), an artificially modified phenyl-urea (N-phenyl-N -1,2,3-thidiazol-5-yl-urea) was also tested for its effect on shoot proliferation. TDZ has been used in the in vitro propagation of various plant species at low concentrations [21,22,39]. The morphogenic response on TDZ media varies depending on the concentration, the type of explant, and genotype.…”
Section: Introductionmentioning
confidence: 99%